Betrayed : a house of night novel - Cast, P. C.; Cast, Kristin (Cast, P. C. House of night, 2007)
After settling in at the House of Night and becoming more comfortable with her vast powers, fledgling vampire Zoey Redbird faces a horrible crisis as human teenagers are becoming victims of a wave of murders and the House of Night becomes the prime suspect.